2017
DOI: 10.1016/j.mseb.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotube-based patch antenna for bandwidth enhancement

Abstract: a b s t r a c tA novel carbon nanotube (CNT)-based rectangular microstrip antenna for wide impedance bandwidth applications has been designed and developed. The copper patch commonly placed on the substrate in a conventional rectangular microstrip antenna is replaced with a CNT patch prepared using spin coating. The MWCNT patch antenna was fabricated by spin coating method and it exhibits an increased impedance bandwidth of 20%. The enhancement of the impedance bandwidth does not affect the broadside radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Our proposed antenna achieves maximum gain of 11 dB, which is 100% larger than existing antenna. Chaya Devi et al 1 developed patch antenna using Multi‐walled copper nano tube and achieved maximum gain of 7 dB at 10 GHz and antenna efficiency of 90%. Our proposed antenna achieves maximum gain of 11 dB, which is 60% more than multi‐walled copper nano tube patch antenna.…”
Section: Performance Comparison Of Proposed Antenna With Other Existing Antennamentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposed antenna achieves maximum gain of 11 dB, which is 100% larger than existing antenna. Chaya Devi et al 1 developed patch antenna using Multi‐walled copper nano tube and achieved maximum gain of 7 dB at 10 GHz and antenna efficiency of 90%. Our proposed antenna achieves maximum gain of 11 dB, which is 60% more than multi‐walled copper nano tube patch antenna.…”
Section: Performance Comparison Of Proposed Antenna With Other Existing Antennamentioning
confidence: 99%
“…Structure of the antenna is again and again optimized to obtain multiband characteristics. Carbon Nano Tube based rectangular microstrip antenna was proposed by Chakaya Devi et al In this work, spin coating machine was used for coating the radiating element over the substrate 1 and author suggested that fabrication technology is used for mass production and also achieved 20% bandwidth expansion. Multi‐process 3D printing technology also is used for patch antenna fabrication 2 and the author identified technical challenges for increasing the performance of the antenna at ISM band.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 However, the use of these conventional materials usually provides narrow bandwidth. 30 , 31 In recent years, many research groups have explored nanomaterials such as graphene, 32 ZnO nanorods, 33 TiO 2 , 34 multiwall carbon nanotubes (MWCNTs), 31 , 35 and so forth, designing the radiating element of the patch antenna. Besides, these nanomaterials have been used in many other photothermal 36 40 and optical device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Brush and rollerball pens have been already employed with metal inks to develop circuits interconnects and passive electronic components (capacitors, resistors and inductors) as well as to combine them into simple circuitry [16,26]. Even handwriting techniques have been already used to develop antennas at different operating frequencies [27,28]. Further, by utilizing these techniques, different kind of sensors have been fabricated.…”
Section: Introductionmentioning
confidence: 99%